Growth Kinetics Modeling and Evaluation of Antiphytopathogenic Activity of Newly Isolated Fungicolous Epicoccum nigrum Associated with Dryad’s Saddle (Polyporaceae) - Radka Baldzhieva; Mariya Brazkova; Denica Blazheva; Bogdan Goranov; Petya Stefanova; Zlatka Ganeva; Desislava Teneva; Petko Denev; Galena Angelova (Agriculture)
In the present study, an unknown fungal strain was isolated from the fruiting body of a local Dryad’s Saddle mushroom (Polyporaceae). The molecular identification of the isolate was performed by amplification of the ITS1-5.8S-ITS2 region and the strain was identified with 100.00% confidence as Epicoccum nigrum. The morphological characteristics, including the distinctive colony pigmentation, conidiophore structure, and conidial shape, were determined to ensure comprehensive characterization of the fungus. The modeling of the kinetics of the growth process was conducted with the applying the logistic curve model and the reverse autocatalytic growth model, and the concentrations of the compounds in the nutrient medium required for the E. nigrum development were established. Controlled submerged cultivation was carried out for cultural liquid obtaining, which was further used for the evaluation of the biological activities. The untreated cultural liquid demonstrated antimicrobial activity against Sclerotinia sclerotiorum where the minimal inhibitory concentration was 1.25 mg/mL. Antimicrobial activity was also detected toward Botrytis cinerea (2.5 mg/mL) and Aspergillus flavus (2.5 mg/mL). The direct utilization of crude cultural liquid for phytopathogenic control is a sustainable approach that will provide the opportunity for the development of an environmentally friendly manufacturing process.